A new approach to tax-exempt bonds: Infrastructure financing with the AGIS bond - Edward V. Regan (Levy Economics Institute of Bard College, 1999)
The current system of tax-exempt bond financing is inefficient and inequitable because a large portion of the federal subsidy provided by the tax exemption does not reach state and local governments and accrues instead to the wealthiest investors. In addition, the current system excludes large institutional investors, both domestic and foreign, with their huge pools of capital, and it lacks the stable oversight characteristic of the taxable bond market. Edward V. Regan and his associates have developed a new security concept to overcome these weaknesses. The American global infrastructure security (AGIS) bond has two components that are sold separately - tax exemption and income flow - creating a taxable bond for sale in the regular capital markets in addition to the tax exclusion benefit.
Keywords: 330